Scalable, high performance, enzymatic cathodes based on nanoimprint lithography - Pankratov, Dmitry; Sundberg, Richard; Sotres, Javier; Suyatin, Dmitry B.; Maximov, Ivan; Shleev, Sergey; Montelius, Lars (Beilstein Journal of Nanotechnology, 2015)
Here we detail high performance, enzymatic electrodes for oxygen bio-electroreduction, which can be easily and reproducibly fabricated with industry-scale throughput. Planar and nanostructured electrodes were built on biocompatible, flexible polymer sheets, while nanoimprint lithography was used for electrode nanostructuring. To the best of our knowledge, this is one of the first reports concerning the usage of nanoimprint lithography for amperometric bioelectronic devices. The enzyme (Myrothecium verrucaria bilirubin oxidase) was immobilised on planar (control) and artificially nanostructured, gold electrodes by direct physical adsorption. The detailed electrochemical investigation of bioelectrodes was performed and the following parameters were obtained: open circuit voltage of approximately 0.75 V, and maximum bio-electrocatalytic current densities of 18 µA/cm2 and 58 µA/cm2 in air-saturated buffers versus 48 µA/cm2 and 186 µA/cm2 in oxygen-saturated buffers for planar and nanostructured electrodes, respectively. The half-deactivation times of planar and nanostructured biocathodes were measured to be 2 h and 14 h, respectively. The comparison of standard heterogeneous and bio-electrocatalytic rate constants showed that the improved bio-electrocatalytic performance of the nanostructured biocathodes compared to planar biodevices is due to the increased surface area of the nanostructured electrodes, whereas their improved operational stability is attributed to stabilisation of the enzyme inside nanocavities.
Keywords: bilirubin oxidase; bio-electrocatalysis; direct electron transfer; nanoimprint lithography; oxygen reduction reaction